Modified Le Fort I Arc Osteotomy Combined With Autologous Bone Grafts to Improve Midface Hypoplasia Combined With Skeletal Class III Malocclusion: A Technical Note. Issue 2 (14th March 2023) - Chen, Kai; Sun, Xiumei; Lin, Yuhui; Wu, Guomin
Abstract : Midface hypoplasia sometimes appears in patients with skeletal class III malocclusion in the Asian population, often requires additional surgical treatments. The technical note is intended to introduce a modified Le Fort I arc osteotomy combined with autologous bone grafts harvested from proximal segments after bilateral sagittal split ramus osteotomy to improve the profile for skeletal class III malocclusion patients with midface hypoplasia. The benefit of the modified technology is that the size and position of the arc can be adjusted according to the severity of the deformity to suit different patients. In addition, the application of autologous bone grafts increased the extra height of osteotomy line and enhanced the surgical effect, and maintained bone consolidation. More importantly, the osteotomy line of the modified Le Fort I arc osteotomy can be easily designed and this modification will not cause additional injuries. Therefore, we believe that for skeletal class III malocclusion patients with midface hypoplasia in Asia modified Le Fort I arc osteotomy combined with autologous bone grafts will be an efficient surgical method to improve midface hypoplasia.